Assessing Plantar Pressure and Feet Pain in Females during the Third Trimester of Pregnancy - Tariq Ahmad, Parveen Shafi, Rahim Khan, Abdul Nabi Ghulam Akbar Khokhar, Syed Alam Zeb, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The centre of gravity is altered in pregnant females resulting in hyperextended knees and resulting pain in the lower back and feet due to postural changes to adapt and recreate balance. The frequency and prevalence of back pain in the second and third trimesters are around 43.6% and 34.8% respectively, whereas the frequency of foot swelling is found to be around 32.6% of pregnant females in the third trimester. Similar trends are observed in overweight non-pregnant females with prevalence trends as the frequency of ankle and feet pain, and knees pain found to be in 68.7% and 53.3% respectively. Aims: This study will aim to assess plantar pressure and feet pain in pregnant females in the third trimester. The study will further assess and compare the severity of symptoms between pregnant females and females who are overweight or obese using a visual analogue scale. Materials and methods: A cross-sectional study was conducted during the period of November 2020 to October 2021. The study was conducted at the Orthopaedic department of Mardan Medical Complex/BKMC, Mardan and Obs and Gynae department of Swabi Medical Complex /GKMC, Swabi. It consisted of 90 females which comprised the study group and control group. The study group consisted of 45 females who were in the third trimester of pregnancy. All the recruited control participants had BMI in the overweight category. The control group consisted of 45 females and the recruitment criteria for the control group as females with Body Mass Index (BMI) ranging between overweight and obese. Both study and control groups were assessed for plantar pressure and foot pain by employing a visual analogue scale for pain severity. Result: The readings showed that the study group 37.7% (17 participants out of 45) complained of an 8/10 severity of pain during the third trimester whereas control participants 24.4% (11 out of 45) showed a 6/10 severity of pain. 91.1% of study group females showed the severity of pain to be 6/10 or more. Results showed that a maximum number of pregnant females had plantar pressure and feet pain similar to or more than that of the control group. Moreover, the control group showed 57.7% of females having symptom severity similar to or greater than 6/10 on the visual analogue scale. Conclusion: The results suggest the prevalence of severe feet pain and plantar pressure is significantly greater in pregnant females in the third trimester with 91.1% as compared to 57.7% of non-pregnant obese females. The severity of pain was also recorded to be higher in pregnant females than in control counterparts.